8 souls eaudiobook - Rust, Rachel (Tantor Media, 2019)
All her life, seventeen-year-old Chessie has had recurring dreams about a little white farmhouse. Quaint? Not quite. The house is the site of the unsolved murders of Villisca, Iowa, where eight people were slaughtered in 1912. With her parents on the verge of divorce, Chessie is stuck spending the summer with her grandparents in Villisca—right across the street from the axe murder house. She's soon hearing voices calling out for help and begins unraveling a link between herself and the town's bloody history. And when she falls for a cute boy harboring a big secret, the pieces fall into place as she at last discovers the truth of Villisca's gruesome past . . .